Arts and Culture Learning Innovation: Development of a Hybrid Learning Model at Arrozaq Rantauprapat Islamic High School - Irda Hayati; Sahat Siagian; Efendi Napitupulu (Randwick International of Education and Linguistics Science Journal, 2024)
The aim of the research is to prove that the hybrid learning model is feasible and effective to use to improve learning outcomes and interest in arts and culture lessons. In this research, the model used is the ADDIE model, namely analysis, design, development, implementation, and evaluation. This research was carried out at Arrozaq Rantauprapat Islamic High School. The research subjects were class students' responses as product users. Based on the recapitulation from the Material Validator Expert Team, an overall average score of 95.38 was obtained, learning design experts obtained an overall average score of 90.71%, and media experts obtained an overall average score of 91%, indicating very effective use based on the Sig value. (2-tailed) obtained a value of 0.007, meaning the Sig value is <0.05. Based on the research data that has been described, it can be concluded that the web-based hybrid learning model developed for arts and culture learning in the dance arts aspect of Arrozaq Rantauprapat Islamic High School is declared very suitable and valid for use.